Development and pilot randomized control trial of a drama program to enhance well-being among older adults. (February 2017) - Moore, Raeanne C.; Straus, Elizabeth; Dev, Sheena I.; Parish, Steven M.; Sueko, Seema; Eyler, Lisa T.
Highlights: Programs are needed to improve well-being in late life. We developed a novel theatre-based program focused on improving well-being. 13 older adults participated in a Drama Workshop (DW) or control condition. Drama instruction may foster happiness, confidence, and self-esteem in late life. Abstract: Objective: Develop a novel theatre-based program and test its feasibility, tolerability, and preliminary efficacy for improving empathy, compassion and well-being among older adults. Method: Thirteen older adults were randomized to a 6-week Drama Workshop (DW) program or time-equivalent Backstage Pass (BP) control condition. Pre- and post-treatment measures included empathy, compassion, and mood scales. Additional post-treatment measures included self-rated change in empathy/compassion, confidence, and affect. Participants also rated their mood/affect after each session. Results: The program was successfully completed and well-liked. No pre-to-post-treatment changes in empathy/compassion or mood symptoms were found in either group. Compared to BP, DW weekly ratings indicated higher levels of anxiety and lower happiness; however, the DW program had higher self-ratings of positive change in self-esteem, confidence, and happiness post-treatment. Discussion: The DW was not shown to promote empathy/compassion. It was also reported as personally challenging. However, engagement in dramatic exercises and rehearsing and performing a dramatic piece was reported by participants as a positive growth experience, as indicated by the post-treatment ratings of enhanced self-esteem, confidence and happiness. Thus, such a program might be useful for counteracting some of the potential negative aspects of older age, including managing physical limitations and coping with losses.